(untitled) (Baghdad Science Journal, 2015)
In this research, main types of optical coatings are presented which are used as covers for solar cells, these coatings are reflect the infrared (heat) from the solar cell to increase the efficiency of the cell (because the cell’s efficiency is inversely proportional to the heat), then the theoretical and mathematical description of these optical coatings are presented, and an optical design is designed to meet this objective, its optical transmittance was calculated using (MATLAB R2008a) and (Open Filters 1.0.2) programs